Estudo comparativo entre o modelo analítico de Domenico (1987) e Wexler (1992) e suas implicações no gerenciamento de passivos ambientais - Yoshinari, Andreia [UNESP] (2014)
The analytical model usually adopted for contaminant transport in groundwater, included the Risk Assessment Worksheet developed by CETESB (2013), is the Domenico (1987) model. This model has mathematical simplifications that, in certain situations, may not satisfactorily reproduce the phenomenon with respect to exact solutions models. This study evaluates the influence of the associated errors of the results of this model in the management of environmental liabilities based on the analysis of human health risk assessment, by comparing the results obtained with the approximate analytical solution of Domenico (1987) and the exact analytical solution of Wexler (1992), as well as to identify which input parameters are the most sensitive in different hydrogeological scenarios by relative sensitivity analysis. To this end, 6 case studies were selected with singularities between them in relation to the aquifer characteristics. Solute transport simulations were performed with the software ETS3D developed by LEBAC-UNESP. The results indicated that the use of the Domenico (1987) model as a primary tool in the study of a contaminated area may be applicable for permeable aquifers (velocity greater than 0,08 m/d) and aquifers of extremely low permeability (velocity less than 0,01 m/d), whose dominant transport processes are either advection or hydrodynamic dispersion, respectively. However, the results must be interpreted with caution for low to intermediate aquifer permeability (velocity between 0,01 m/d and 0,08 m/d), where the processes of advection and hydrodynamic dispersion are of equal importance. These situations may lead to different results of potential risk, and may consequently lead to different decision-making in the management of environmental liabilities. The input parameters of the source dimension in the y-axis, hydraulic conductivity (Kx) and longitudinal dispersivity (alpha x) are the parameters that showed intermediate to high...